Integrasi Global Citizenship dan Nilai Pangèsto Dalam Pendidikan Islam Moderat di Madura - Achmad Firdausi; Mohammad Muchlis Solichin; Faidl Royhan (LPPAIK Universitas Muhammadiyah Bandung, 2026)
Moderate Islamic education in Madura requires a conceptual formulation that is able to connect local wisdom, Islamic values and awareness of global responsibility. However, regarding global citizenship in Islamic education, it is still relatively limited in placing Pangèsto as a local Madura ethic that reflects gratitude, reciprocity, and prosocial responsibility. The article aims to formulate an integration model between global citizenship, Pangèsto values and moderate Islamic education. This study uses a qualitative-descriptive approach with a literature study type. Data were analyzed through thematic content analysis of literature that discusses global citizenship, religious moderation, Islamic education, Madura local wisdom, and the theory of gratitude and prosocial responsibility. This study shows that Pangèsto is not only understood as a practice of repaying personal services, but also as a local form of gratitude, moral reciprocity, and prosocial responsibility. In moderate Islamic education, Pangèsto values have a slice of values with gratitude, manners, and ihsan, ukhuwah, tasamuh, and humanitarian responsibility. When integrated with global citizenship, the meaning of Pangèsto has expanded from individual reciprocity to social responsibility towards society, nation, humanity, and the environment. This article offers an integrative framework in the form of: Pangèsto as a local value of Madura – moderate Islamic values / adab and gratitude – global citizenship based on empathy, solidarity, peace, justice, and social-environmental responsibility.